IMPORTANCE OF RETAIL DISPLAY IN IMPULSE BUYING DECISION (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The current research aims to explore the  importance of retail display on consumer  impulse buying behavior. Exactly, this paper  researched the influence of window display,  promotional signage, store layout, background  music and store smell on consumer impulse  purchase behavior. The research was conducted  among 117 customers of Delhi Retail Stores  using questionnaire which was formulated based  on the previous literature. The collected data  was analyzed using factor analysis and linear  regression tests. The research findings suggested  that store attributes including window display,  promotional signage and smell play important  role in influencing the impulse buying behavior  of customers. Final chapter of the current  research provides some recommendations for  store managers on further improvement of store  atmosphere to encourage impulse buying among  customers.
Keywords: Impulse buying; retail display; store attributes; buying behavior; factor analysis; regression